Incidence and outcomes of ruptured abdominal aortic aneurysms in rural and urban Australia. Issue 11 (30th January 2013) - Shiraev, Timothy; Condous, Michael G.
Abstract: Background: Rural and regional populations suffer higher rates of preventable disease and all‐cause mortality than urban areas, with rural areas of the USA experiencing double the rate of ruptured abdominal aortic aneurysms (AAAs). We investigated the incidence and outcomes of ruptured AAAs in an Australian rural and regional setting, and compared these with those of an urban population. Methods: We undertook a retrospective analysis of all patients suffering AAA rupture in New South Wales (NSW) from 2009/2010 to 2010/2011. Variables included rates of rupture, mortality and intensive care admission. Urban and rural–regional areas were stratified according to NSW Health Local Health Districts, and comparisons between the two groups were performed. Results: Ruptured AAAs had an incidence of 4.1/100 000, with males twice as likely to suffer AAA rupture ( P = 0.009), but females 88% more likely to die from rupture ( P = 0.001). There was no significant difference between AAA rupture rates (5.0 versus 3.4 per 100 000; P = 0.054) nor case‐fatality rates (41.22% versus 40.94%; P = 0.087) in rural–regional and urban populations. Patients in urban areas had a longer hospital stay (5 days versus 1 day, P = 0.001), were more likely to be admitted to intensive care unit (29.4% versus 19.9%, P = 0.001) and were less likely to be transferred to another hospital (19% versus 32%, P = 0.001). Conclusions: AAA ruptures remain a significant public health burden. Rural and regional areas suffer disproportionately, which may be improved by implementation of AAA screening and funding for rural and regional hospitals to sustain adequate surgical and intensive care facilities.